Children’s Boarding School in Indonesia: Examining Psychological and Social Dynamics in the Perspective of Gender-Friendly Islamic Boarding Schools - Ningsih Fadhilah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The purpose of this research is to find out the psychological dynamics in children's boarding schools, which focus on the problems of the psychological well-being of young students who are felt to be in the boarding school environment as well as the challenges of boarding schools in fulfilling the psychological well-being of students in the perspective of genderfriendly boarding schools. This research is qualitative research with the type of Field Research and uses a phenomenological paradigm. The research subjects were students of school age, namely 6-12 years. Through interviews, observation, and documentation, data was collected for both the santri and the caretakers of the boarding schools (kiai or nyai). Data analysis uses the Miles and Huberman model, through four steps, namely data collection, data reduction, data display, and conclusion. The results showed that there were still some conditions for students who experienced psychological turmoil during the adjustment period, such as homesickness, self-acceptance, difficulties in establishing social relations with other friends problems of independence, especially for low-class students and at the beginning of the boarding year. A gender-biased perspective was found in fulfilling children's rights in Islamic boarding schools, such as the assumption that looking after women is more difficult than men, women have to take extra care of themselves and their morals while men are labeled as difficult to manage, and tend to be naughty. Besides that, the fulfillment of nutrition and balanced nutrition is not found in Islamic boarding schools with the reason for developing the principle of zuhud (simplicity). This is what makes it a particular challenge for Islamic boarding schools to help the growth and personal development of students so that they feel comfortable and happy in the boarding school with all the activities and activities that bind students, both male and female students. This challenge is very important to be captured by pesantren managers such as forming child-friendly pesantren.